ANALISIS PENGARUH FRAUD PENTAGON TERHADAP FRAUDULENT FINANCIAL REPORTING DENGAN MENGGUNAKAN MODEL ALTMAN (STUDI EMPIRIS PADA PERUSAHAAN SEKTOR KEUANGAN DAN PERBANKAN DI INDONESIA) - B2092161004, Junardi (MAKSI UNTAN, 2018)
This research aims to examine the fraud elements in the fraud pentagon theory toward an indication of the existence of fraudulent financial reporting in the company’s financial and banking sector in Indonesia in 2014-2016. Independent variable used in this research are financial target, financial stability, external pressure, personal financial need, ineffective monitoring, external auditor quality, change in auditor, audit opinion, change in board of directorfrequent number of CEO’s picture and CEO politicians while dependent variable used is fraudulentfinancial reporting which is proxied with Altman Z’Score.This research using 201 of sample derived from 67 company in financial and banking sector that registered at Bursa Efek Indonesia (Indonesia Stock Exchange) in 2014-2016. This research performed with quantitative methods using secondary data. The secondary data derived from financial reporting that is downloaded via company website and BEI. Sample size determination using purposive sampling. Data analysis using the multiple linear regression methods.The result of this research shows the existence of one significant influential variable in detecting the occurrence of fraudulent financial reporting, i.e. financial target. The variable represents an element in the fraudpentagon theory i.e. pressure. The existence will occur when the high performance of the company in a previous year, will affect the earning profit target in the following years so that such conditions will inflict to management to achieve an earning profit target in following years at least equal or higher profits earned in previous years. Keyword: Fraud, Fraud Triangle, Fraud Diamond, Fraud Pentagon, Fraudulent Financial Reporting, Altman Z’Score